2006
DOI: 10.1002/ajh.20836
|View full text |Cite
|
Sign up to set email alerts
|

The study of sequence configuration and functional impact of the (AC)n(AT)xTy motif in human β‐globin gene promoter

Abstract: In this report we examine the (AC) n (AT) x T y motif residing À530 bp 5 0 upstream of the b-globin gene in Chinese thalassaemic patients. This motif is a putative binding site for a repressor protein, termed beta protein 1 (BP1) (Berg et al., Nucleic Acids Res 1989;17:8833-8852). Variations in the (AC) n (AT) x T y repeats affect the binding affinity of BP1, thereby altering the expression of the b-globin gene. Eight different configurations of this repeat motif are identified in our population of Chinese b-t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2008
2008
2013
2013

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 19 publications
0
3
0
Order By: Relevance
“…(17, 23) This particular AT repeat motif was associated with the lowest HBB mRNA expression in differentiated MEL cells. (24) A similar AT motif was associated with β thalassemia in carriers without a detectable mutation in HBB. (25, 26) HBB suppression might play a role in the high level of γ-globin gene expression found with the AI haplotype.…”
Section: Discussionmentioning
confidence: 97%
“…(17, 23) This particular AT repeat motif was associated with the lowest HBB mRNA expression in differentiated MEL cells. (24) A similar AT motif was associated with β thalassemia in carriers without a detectable mutation in HBB. (25, 26) HBB suppression might play a role in the high level of γ-globin gene expression found with the AI haplotype.…”
Section: Discussionmentioning
confidence: 97%
“…An interesting study by Chan et al (2007) showed association between the (AC) 3 (AT) 7 (T) 5 configuration and raised HbF levels among the Chinese population 24. They suggested that (AC) n (AT) x (T) y configuration may have an association with the HPFH phenotype which acts by suppression of the β globin gene expression.…”
Section: Discussionmentioning
confidence: 99%
“…To search for genetic determinants of different levels of HBG gene expression we first carried out an extensive sequence analysis of putative regulatory regions within the HBB cluster that were potentially involved in these mechanisms. We examined sequence variations in binding sites for transcriptional factors or in polymorphic sequences within the hypersensitive site‐2 (HS‐2) of the locus control region (LCR) (Öner et al , 1992) and the promoter region of the HBG2 and HBB genes (Berg et al , 1991; Pissard & Beuzard, 1994; Chang et al , 1995; Lu & Steinberg, 1996; Chan et al , 2007), all of which had been reported to be involved in modulation of globin gene expression (Table II). The same HBB cluster genotype was found in the three patients and we were able to exclude known HPFH mutations and hypothetical parental germ line rearrangements within this locus.…”
Section: Resultsmentioning
confidence: 99%